Knowledge, Attitude and Practice of Disaster Preparedness Among Health Care Workers in a tertiary care center of Central Nepal - Thapa, Rashmi; Yadav, Mandeep Kumar; Pokharel, Mohir; Chhetri, Dinesh; Neupane, Durga; Mandal, Sobha; Shahi, Makendra Bahadur (Journal of Karnali Academy of Health Sciences, 2022)
Background: An increase in the number of natural disasters and consequently the rate of disability has been also increased. So, purpose of this study is to assess the knowledge, attitude and practice about disaster preparedness among health care workers at a tertiary care center of a disaster-prone developing country like Nepal. Methods: This is a descriptive cross-sectional study. A total of 135 participants were included. Self- administered multiple sets of questionnaires with four sections i.e., Demographic information, Knowledge Questionnaire, Aptitude Checklist, and Practice based questionnaire were used for study. The study was conducted in Kathmandu Medical College Teaching Hospital and the study period was two months, from December 2021 to February 2022. The respondents were the staffs working in Kathmandu medical college teaching hospital with or without formal training and work-related experiences of disaster preparedness and management in the past. The data was entered into the Microsoft Excel software and analyzed using the statistical package for social studies (SPSS) software 23.0 version and P-value was set at 0.5 with 95% CI. Results: Among 135 participants, female participants were 90 (66.7 %). There were 41 Doctors (37.0%) and 45 nurses (37.8%). Equal participation from every department was ensured. Their overall knowledge, attitude, and practice in disaster preparedness were good. 80.7% of the participants had knowledge of the disaster, and 7.0% agreed with the necessity to have a disaster plan. Conclusions: Health Care professionals have a significant level of knowledge. Attitude is a significant predictor of readiness to practice. Educators and health policymakers should build a robust curriculum in disaster medicine management and preparedness for the future of competent health care professionals in our country Nepal